2003
DOI: 10.1038/nature02078
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously emerging cortical representations of visual attributes

Abstract: Spontaneous cortical activity--ongoing activity in the absence of intentional sensory input--has been studied extensively, using methods ranging from EEG (electroencephalography), through voltage sensitive dye imaging, down to recordings from single neurons. Ongoing cortical activity has been shown to play a critical role in development, and must also be essential for processing sensory perception, because it modulates stimulus-evoked activity, and is correlated with behaviour. Yet its role in the processing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

89
807
7
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 868 publications
(907 citation statements)
references
References 29 publications
89
807
7
4
Order By: Relevance
“…We think this reflects dynamically stable priors for the hypothesis that the environment has line segments of different distinct orientations. In other words, this is something the visual system is always expecting (Hubel & Wiesel, 1962;Kenet, Bibitchkov, Tsodyks, Grinvald, & Arieli, 2003). Therefore, when no higher level hypotheses are involved and when there is enough uncertainty or noise in the system (e.g., blurring), the system will try to predict the scene for line segments rather than meshes.…”
Section: Monocular Rivalrymentioning
confidence: 99%
“…We think this reflects dynamically stable priors for the hypothesis that the environment has line segments of different distinct orientations. In other words, this is something the visual system is always expecting (Hubel & Wiesel, 1962;Kenet, Bibitchkov, Tsodyks, Grinvald, & Arieli, 2003). Therefore, when no higher level hypotheses are involved and when there is enough uncertainty or noise in the system (e.g., blurring), the system will try to predict the scene for line segments rather than meshes.…”
Section: Monocular Rivalrymentioning
confidence: 99%
“…it has been demonstrated that cortical networks often spontaneously approach states similar to orientation maps [3,35]. Furthermore, the variability of responses of individual cells is in part attributable to cortical states across broad regions of the network [4].…”
Section: Pattern Adaptation-induced Orientation Shifts At Pinwheel Cementioning
confidence: 99%
“…Furthermore, the variability of responses of individual cells is in part attributable to cortical states across broad regions of the network [4]. The spontaneous activity of neurons can also reflect the functional circuit of which the neuron is a part [3,35].…”
Section: Pattern Adaptation-induced Orientation Shifts At Pinwheel Cementioning
confidence: 99%
“…Importantly, intrahemispheric, spontaneous infraslow activity exhibits a patterned regional structure that is analogous to cortical motifs within higher-frequency (0.5-6 Hz) activity that we have previously described 27 . This builds upon pioneering studies in cat visual cortex which illustrated that cortical orientation representations are dynamically represented in ongoing spontaneous activity, and further, that these events may serve a preparatory role in setting default cortical sensory input parameters 30,31 .…”
mentioning
confidence: 99%